2022
DOI: 10.1590/1413-81232022272.46012020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of common mental disorders among Brazilian workers: systematic review and meta-analysis

Abstract: The aim of the present study was to summarize the prevalence of common mental disorders (CMD) among Brazilian workers through a systematic review and meta-analysis. Searches were conducted in SciELO, LILACS, PubMed, Scopus, and Web of Science. Articles were included if they had; an observational design, a sample of Brazilian workers, used a validated instrument and cut-off to assess CMD, and provided the prevalence value. A random-effect meta-analysis using professional categories as subgroups and a meta-regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
4
0
1
Order By: Relevance
“…The worldwide prevalence of CMDs in the general population was estimated at 29.2% [95% confidence interval (95%CI) 25.9;32.6], according to a systematic review that evaluated studies between 1980 and 2013. 2 In Brazil, another systematic review published in 2022, 3 found similar results, in which the prevalence of CMDs was 30.0% (95%CI 27.0;34.0).…”
Section: Introductionmentioning
confidence: 69%
“…The worldwide prevalence of CMDs in the general population was estimated at 29.2% [95% confidence interval (95%CI) 25.9;32.6], according to a systematic review that evaluated studies between 1980 and 2013. 2 In Brazil, another systematic review published in 2022, 3 found similar results, in which the prevalence of CMDs was 30.0% (95%CI 27.0;34.0).…”
Section: Introductionmentioning
confidence: 69%
“…Prevalências mais próximas e até mesmo superiores àquelas observadas entre servidores e magistrados em nosso estudo foram verificadas entre trabalhadores da saúde (43%) 45 e entre professores da educação infantil e ensino fundamental (53%) 11 . O estudo de revisão sistemática e meta-análise realizado por Coledam et al 46 verificou prevalência global de sofrimento psíquico entre trabalhadores brasileiros em torno de 30%, sendo que categorias como bancários e professores apresentaram prevalências mais próximas àquelas observadas entre magistrados e servidores, respectivamente.…”
Section: Resultsunclassified
“…For instance, a systematic review and meta-analysis with Brazilian workers showed a 30% prevalence of CMD in the general population [27] A study conducted before the pandemic observed that 50% of public healthcare workers felt nervous, tense, or worried, 20% felt tired all the time, 26%…”
Section: Discussionmentioning
confidence: 99%